Toward Supporting Personalized Tracking Experiences in Healthcare - Choe, Eun Kyoung; Lee, Bongshin (Interactions, 2020)
This forum is dedicated to personal health in all its many facets: decision making, goal setting, celebration, discovery, reflection, and coordination, among others. We look at innovations in interactive technologies and how they help address current critical healthcare challenges. — Yunan Chen, Editor